(untitled) (Proceedings of International Educators Conference, 2024)
The development of new technologies and the pace of implementation of completely new types of goods and services based on them lead to the fact that the market situation and consumer needs are changing more and more. The consumer says what he wants to buy, where, how he looks and at what price.